Working Under Dictatorship: Discipline, Violence, And Silence - Vergara, Angela (Revista de Historia Social y de las Mentalidades, 2023)
This essay discusses the impact of the coup d’état on Chilean workers. By 1973, entrepreneurs were increasingly concerned about the lack of discipline in the workplace. The military coup offered them a new opportunity to regain control over the workforce and production, task that they delegated into the armed forces. Based on the analysis of human rights accounts and legal cases of people fired for political reasons, I show how the dictatorship sought to “normalize” relations within the factory, which will support future transformations.